R. Angus K. Smith, Mary K. Dabney, Evangelia Pappi, Sevasti Triantaphyllou and James C. Wright. Ayia Sotira. A Mycenaean chamber tomb cemetery in the Nemea Valley, Greece - Dickinson , Oliver (Journal of Greek Archaeology, 2019)
This volume publishes a group of 6 chamber tombs excavated at the south end of the Nemea valley, not much more than a kilometre to the north-west of the settlement of Tsoungiza, which itself lies a similar distance slightly to the north-west of the historical Sanctuary of Zeus, site of one of the four regular festivals of Panhellenic athletic contests. Tsoungiza was a long-lived settlement, originally founded in the Early Bronze Age but abandoned for much of the Middle Bronze Age and only resettled in the phase in which the foundations of Mycenaean civilisation were being laid.